Pengaruh Literasi Perpajakan dan Digitalisasi Pajak terhadap Kepatuhan Wajib Pajak Mahasiswa Akuntansi Universitas Bina Sarana Informatika - Syahla, Farelia Naurah; Purwatiningsih, Rosita Tri; Kusuma, Dian Putri Ayu; Anggraini, Ria (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Low taxpayer compliance remains a persistent challenge in Indonesia, particularly among prospective taxpayers such as university students. This study aims to examine the effect of tax literacy and tax digitalization on taxpayer compliance among accounting students at Bina Sarana Informatika University, Slipi Campus. A quantitative research design was employed using primary data collected through structured questionnaires distributed to 74 students selected by random sampling. Tax literacy, tax digitalization, and taxpayer compliance were measured using Likert-scale indicators. The collected data were analyzed using multiple linear regression with SPSS version 21, preceded by validity, reliability, and classical assumption tests. The findings reveal that tax literacy has a positive and significant effect on taxpayer compliance, indicating that a higher level of understanding of tax regulations encourages more compliant behavior. In contrast, tax digitalization does not show a significant effect on compliance when examined individually, suggesting that technological availability alone is insufficient to shape compliance behavior. However, when analyzed simultaneously, tax literacy and tax digitalization jointly have a significant influence on taxpayer compliance. These results highlight the importance of strengthening tax education while aligning digital tax systems with users’ readiness to ensure sustainable compliance in the future.